A Necessary Constraint on the Use of Extended Harmonic Analysis for Tide Predictions - Zetler, Bernard D. (The International Hydrographic Review, 2015)
When American and British tide researchers, in an effort to improve tide predictions for large-range shallow-water tides, greatly expanded the number of tide constituents (extended harmonic analysis), they chose the added frequencies by selecting peaks of energy greatly exceeding the continuum (noise level) in a high-resolution Fourier analysis of tide residuals (observed minus predicted). Unfortunately, some tide agencies are now routinely analyzing for a greatly expanded number of constituents without checking as to whether the amplitudes of these added constituents are significantly larger than the continuum. They do this believing that more is necessarily better; actually, in some cases, a future prediction may be worse unless this check is done routinely.